Wifi-UHF transceiver design for 650-680 MHZ television white space (TVWS) spectrum application - Khairil Anuar Khairi (School of Computer and Communication Engineering, 2018)
Study has embarked on understanding the insight of TV white space technology which includes the frequency range coverage, the current utilization of the frequencies, the frequencies availability and the necessary frequency range to be used for WUT application as the design for a white band application might be too challenging and needs extremely huge efforts. In order to improve the coverage of data communication over Wi-Fi, WUT deploys a concept which is quite similar to transceiver where the signal through the WUT will be up and down-convert to enable the data transfer between two Wi-Fi modems. Thus the design architecture of proposed WUT assembled a basic transceiver system which includes two main elements: transmitter and receiver consisting of sub-components such as RF filters, amplifiers, circulators, attenuators, mixers and VCO-PLL.